DROGADIÇÃO NA INFÂNCIA E ADOLESCÊNCIA: O ABUSO DE DROGAS COMO SINALIZADOR DE NECESSIDADES DE MUDANÇAS NAS FAMÍLIAS - DOZA, ANDERSON C.; MEDEIROS, BRUNO B.; BOSSARDI, CARINA N.; BREITENBACH, CRISTIANE A.; TATSCH, DIRCE T.; FELIPPO, FERNANDA D.; ZANCANARO, JOÃO R.; MAURINA, LEDA R. C.; FÁVERO, MARÍNDIA; CEDRON, MÁRCIA; et al. (Salão do Conhecimento, 2013)
Resumo